A Raman spectroscopic method for determining vapour liquid equilibria - Adami, Renata; Schuster, Julian; Liparoti, Sara; Reverchon, Ernesto; Leipertz, Alfred; Bräuer, Andreas (Fluid Phase Equilibria, 2013)

A Raman technique applicable for the analysis of the working principle of promoters and inhibitors of gas hydrate formation - Will, Stefan; Bräuer, Andreas; Hankel, Robert; Mehnert, Markus; Schuster, Julian (Journal of Raman Spectroscopy, 2015)
We report a Raman technique applicable for the in situ analysis of the development of hydrogen bonds in the liquid water-rich phase just before the onset of gas hydrate formation. Herewith, the phase transition as well as the working principle of hydrate formation inhibitors and promoters can be analyzed. (C) 2015 The Authors. Journal of Raman Spectroscopy published by John Wiley & Sons Ltd.
Keywords: gas hydrate; inhibitor; Raman spectroscopy; hydrogen bond; OH stretch vibration

Deconvolution of Raman spectra for the quantification of ternary high-pressure phase equilibria composed of carbon dioxide, water and organic solvent - Will, Stefan; Schuster, Julian; Leipertz, Alfred; Bräuer, Andreas (Journal of Raman Spectroscopy, 2014)
The paper reports on a routine to extract the composition of multi-component mixtures from their Raman spectra at elevated pressures. The strategy is based on fitting weighted Raman spectra of the pure compounds to the measured Raman spectrum of the mixture, also considering the effects of intermolecular interactions onto the Raman spectra by applying Gaussian and Voigt profile deconvolution of the Raman peaks. Thereby, an improved accuracy compared to previous evaluation strategies could be obtained. The more accurate data of the ternary mixtures of carbon dioxide, water and organic solvents are presented. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: quantitative Raman spectroscopy; Raman spectra evaluation; phase equilibrium; mixture composition; high pressure

In situ Raman quantification of the dissolution kinetics of carbon dioxide in liquid solutions during a dense phase and ultrasound treatment for the inactivation of Saccharomyces cerevisiae - Ferrentino, Giovanna; Schuster, Julian; Bräuer, Andreas; Spilimbergo, Sara (Journal of Supercritical Fluids, 2016)

Non-invasive quantification of phase equilibria of ternary mixtures composed of carbon dioxide, organic solvent and water - Luther, Sebastian; Schuster, Julian; Leipertz, Alfred; Bräuer, Andreas (Journal of Supercritical Fluids, 2013)

Remote analysis of high pressure phase equilibria in micro capillary flows - Schuster, Julian; Luther, Sebastian; Will, Stefan; Bräuer, Andreas (28th European Symposium on Applied Thermodynamics, 2015)

Shining light on low-temperature methanol aqueous-phase reforming using homogeneous Ru-pincer complexes – operando Raman-GC studies - Strobel, Vinzent; Schuster, Julian; Bräuer, Andreas; Vogt, Lydia; Junge, Henrik; Haumann, Marco (Reaction Chemistry & Engineering, 2017)

Simultaneous analysis of the dispersed liquid and the bulk gas phase of water sprays using Raman spectroscopy - Schuster, Julian; Siegler, Philipp; Günther, Astrid; Wirth, Karl-Ernst; Bräuer, Andreas (Applied Spectroscopy, 2016)

Thermodynamic characterization of water and alcohol sprays using Raman spectroscopy - Schuster, Julian; Siegler, Philipp; Bräuer, Andreas; Will, Stefan (28th European Symposium on Applied Thermodynamics, 2015)